Pengaruh Kualitas Sistem, Kualitas Informasi, Kualitas Layanan, dan Persepsi Manfaat Terhadap Kepuasan Pengguna Aplikasi SIPD - Febrianti, Triska; Fiddin, Fachroh (Politeknik Negeri Bengkalis, 2024)
This study aims to determine the effect of system quality, information quality, service quality, and perceived benefits on user satisfaction of the Regional Government Information System (SIPD) application in Bengkalis Regency. A sample of 58 respondents from 29 Regional Work Units (SKPD) who were directly involved with the SIPD application was collected using purposive sampling. Research using quantitative methods. The data collection technique used a questionnaire method with a Likert scale and was analysed using multiple linear regression. The results showed that system quality and information quality have no effect on user satisfaction while service quality and perceived benefits affect user satisfaction with the SIPD application. These results of this study are supported by Delone & Mclean IS Success Model and Technology Acceptance Model.Keywords: System Quality, Information Quality, Service Quality, Perceived Usefulness and User Satisfaction.